Against Theory of Mind
VII, 273 p.
Keywords: The 'theory of mind' framework has been the fastest growing body of empirical research in contemporary psychology. It has given rise to a range of positions on what it takes to relate to others as intentional beings. This book brings together disparate strands of ToM research, lays out historical roots of the idea and indicates better alternatives.